The existence of Pelinggih Ratu Niang Sakti as an environmental conservation effort in supporting Sad Kertih Loka Bali - Ni Putu Winanti (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Introduction: This study discusses Pelinggih Ratu Niang Sakti as an environmental preservation effort in supporting Sad Kertih Loka Bali. Hindus in Bali have literature on the preservation of the inner environment, which is used in ceremonies such as Bhuta yadnya, ceremonies on tumpek bubuh or tumpek pengatag days, and Tri Hita Karana teachings. In addition, the problem of the natural environment, especially with regard to waste, is still a problem that has not been resolved. One form of environmental preservation that is carried out indirectly is the existence of the Ratu Niang Sakti temple. Methods: This study is analyzed using the Ethnographic Content Analysis (ECA) method and the data is presented in qualitative form. Finding: The existence of Pelinggih Ratu Niang Sakti as an environmental conservation effort in supporting Sad Kertih Loka Bali includes three things, namely (1) as a harmonizer of Tri Hita Karana teachings; (2) as biological preservation, and Hindu theo-ecology; and (3) supporting Sad Kertih Loka Bali, especially in the field of wana kertih. Conclusion: From the point of view of Hindu Theo-ecology, the existence of Pelinggih Ratu Niang Sakti is also related to efforts to preserve the natural environment, such as wana kerthi, which means glorifying forests and trees in Bali. The large trees that accompany the Pelinggih Ratu Niang Sakti, especially the kepuh tree (Sterculia foiteda), a type of kapok or randu tree that is tall with a towering trunk, is often found in the coastal forests of Bali and also in Java